Pengaruh Variabel Fundamental dan Makro Ekonomi terhadap Harga Saham (Studi pada Perusahaan yang Masuk dalam Indeks LQ45) - Suselo, Dedi; Djazuli, Atim; Indrawati, Nur Khusniyah (Universitas Brawijaya, Indonesia, 2015)
The LQ45 index constitutes good stocks that classify into liquid category. The research aims to investigate the influence of fundamental and macroeconomic variables on stock prices in the LQ45 index during the period 2010 to 2013. The population in this research are 30 companies in the LQ45 index. The analysis method of the research uses liniermultiple regression. The results of the reseatrch indicated that ROA, PBV, EPS, PER and the sensitivity of interest rate has significant positive effect on stock prices. ROE, the sensitivity of exchange rate and the sensitivity of inflation has significant negative effect on stock prices. DER has no significant effect on stock prices. The research contributed to the developmentof the science of management and investment, especially the influence of DER towards stock prices.